Crisis-led transformation or no transformation at all? A multifaceted inquiry towards destination recovery - Singh, Ramjit; Dogra, Jeet; Mir, Mudasir Ahmad; Karri, Venkata Rohan Sharma (Turyzm/Tourism, 2023)
Though there has been an upward rise in the number of publications on COVID-19, tourism and hospitality, researchers have turned a blind eye towards conducting a multifaceted stakeholder assessment of its impact on a given destination and the possible effects of recent developments on the destination’s recovery. To address the latent gap, this study first attempts to assess the impact of COVID-19 on various aspects of a destination’s businesses, workforce and the local community. Taking into consideration the recent pharmaceutical developments and ease in travel restrictions, it then explores the effects of such an intervention on the destinations’ recovery process. 142 valid questionnaires were collected from employees of travel agents, tour operators, transport operators and hotels in the northern part of India. Subsequently, PLS-SEM (partial least squares structural equation modeling) was applied using SmartPLS to test the proposed hypotheses. Through two individual studies in September 2020 and November 2021 i.e. at different stages of the pandemic, this study not only offers insights into the current status of destination recovery but also tests the validity and applicability of recent publications, their proposed recommendations and future practices. Recovery at a destination was found to be a result of the recovery of its businesses, workforce and community. These factors also had positive and negative impacts on each other. The article further suggests the low transformational ability of the pandemic in the context of tourism and hospitality. It is amongst the first few studies to have carried out a temporal assessment of stakeholders for an investigation into the pandemic’s impact on destinations in addition to their recovery.